Evaluation of bitumen intervals in the carbonate reservoir, case study in Y oilfield of Iran. (17th January 2018) - Zhang, Shimao; Zhang, Shaonan; Ge, Xiang; Zhang, Yun
ABSTRACT: The bitumen intervals, which were drilled at Y oilfield of Iran, often reduce drilling efficiency. The characteristics of high natural gamma radioactive(GR), low uranium-free gamma(KTH), and poor GR-KTH relationship have been found to detect the bitumen by logging. Conventional porosity logs, Poisson's ratio, the P & S-wave velocity ratio and the wave impedance, derived from logging, can be used to identify the heavy oil bitumen. The bitumen distribution can be predicted by the log interpretation. Implementation of log evaluation allows better solving the bitumen intervals identify problems, and also to helps in enhancing development efficiency in the similar petroleum reservoirs.